Propagation of solitons for the Hamiltonian amplitude equation via an analytical technique - Tarla, Sibel; Ali, Karmina K.; Yilmazer, Resat; Osman, M. S. (World Scientific Publ Co Pte Ltd, 2022)
This study investigates the Hamiltonian amplitude equation by using the generalized exponential rational function method. As a result, a variety of soliton solutions have been established with different wave structures such as optical exponential, dark, singular, periodic, periodic-singular, and hyperbolic solutions. 2D and 3D graphics of certain acquired solutions are drawn with the help of computer program. By picking appropriate values for the free parameters in the obtained solutions, the physical phenomena for these obtained solutions are graphically studied and depicted.
Keywords: Hamiltonian amplitude equation; generalized exponential rational function method; soliton solutions; exact solutions